Aphid species (Hemiptera: Aphididae) reported for the first time in Tucumán, Argentina - Avila, Ana Lucía; Vera, M. Alejandro; Ortego, Jaime; Ploper, Leonardo Daniel; Conci, Vilma Cecilia (2018)
Aphids (Hemiptera: Aphididae) are considered among the most important pests all around the world. The total number of aphid species recorded in Argentina between 2003 and 2013 has risen from 200 to 237, which demonstrates the continuous introduction and discovery of new species in the territory. Therefore, faunistic studies should be conducted without interruption in areas of interest. The aim of this study was to establish if there were aphid species in Tucuman Province, Argentina that had not been recorded previously in the province. Aphids were collected with modified Moericke yellow water pan traps in potato crops during 2 seasons in 3 regions of Tucumán. Seventeen species, among the 47 species identified, and the genus Illinoia represent new records for the Province.